Examining the Degree of Compliance of Cybernetic Components in the Comprehensive Statistical System: A Case Study of Iran Public Libraries Foundation - Mostafa Ahangar; Hassan Behzadi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Objective: This research aims to examine the alignment of cybernetic components with the statistical system of Iran Public Libraries Foundation. Method: This applied research used the qualitative content analysis of the Public Libraries' Statistical System. Data was collected through library and documentary research, applying a case study approach. A content analysis strategy was employed to assess the alignment of cybernetic components. Results: Essential components for cybernetic systems, include aim, input, processing, output, communication, control, and feedback were examined in the statistical system document. While terminology varied, the processes served their intended purposes. The strongest components were "input, processing and transformation, and output", "control," and "feedback" with "goal" states and “aim” and "communication" ranked average, indicating the solid alignment. Conclusions: The compatibility of these components with the statistical system developed by the Statistical Research Institute of Iran suggests a systemic perspective in statistical processes without the explicit mention of cybernetics. This alignment enhances the credibility of the system and improves decision-making in Iran's public libraries. The research can model the application of cybernetic components in other information systems and support the development of cybernetic theories in managerial contexts.